Clinical pharmacology of infusion fluids - G.Hahn, Robert (Acta medica Lituanica, 2012)
Fluids are used for intravenous infusion during practically all surgeries, but several different compositions are available on the market. Crystalloid fluids comprise lactated or acetated Ringer solutions, normal saline, Plasma-Lyte, hypertonic saline, and glucose. They lack allergic properties but are prone to cause peripheral tissue oedema. Their turn over is governed by physiological factors such as dehydration and drug effects. Colloid fluids include hydroxyethyl starch, albumin, dextran, and gelatin. These fluids have various degrees of allergic properties and do not promote peripheral oedema. Their half-life is usually about hours. Factors increasing the turnover rate are poorly known but might include inflammatory states. Current debates include the widespread use of normal saline, which should be replaced by Ringer’s or Plasma-Lyte in most situations, and the kidney damage associated with the use of starch in septic patients. New studies show that hypertonic saline does not improve survival or neurological damage in prehospital care.
Keywords: Ringer solution – hydroxyethyl starch – model; pharmaco kinetic; fluids; i. v.